2022
DOI: 10.1609/aaai.v36i11.21555
|View full text |Cite
|
Sign up to set email alerts
|

An Experience Report of Executive-Level Artificial Intelligence Education in the United Arab Emirates

Abstract: Teaching artificial intelligence (AI) is challenging. It is a fast moving field and therefore difficult to keep people updated with the state-of-the-art. Educational offerings for students are ever increasing, beyond university degree programs where AI education traditionally lay. In this paper, we present an experience report of teaching an AI course to business executives in the United Arab Emirates (UAE). Rather than focusing only on theoretical and technical aspects, we developed a course that teaches AI w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Uncertainties persist in many aspects, such as effectiveness, implementation strategies, and potential impact of AI interventions (Sharfi, 2021). There are a number of studies in the region showing positive impact of AI interventions in higher education, such as making it easy for instructors to grade students (Al-Hashimi and Hamdan, 2021) and improving students' understanding on how to incorporate technology into the existing business process (Johnson et al, 2022). However, a number of studies reflect significant obstacles and issues, such as inadequate training of faculty members (Aldossary et al, 2020), failure to follow up and monitor challenges for adopting AI (Albasalah et al, 2021), stress and pressure among teachers due to feeling AI is challenging their position , as well as the scarcity of resources, lack of investment in AI, poor interest in college administration, lack of knowledge, and a limited number of studies that are associated with the AI applications (Mohammad et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainties persist in many aspects, such as effectiveness, implementation strategies, and potential impact of AI interventions (Sharfi, 2021). There are a number of studies in the region showing positive impact of AI interventions in higher education, such as making it easy for instructors to grade students (Al-Hashimi and Hamdan, 2021) and improving students' understanding on how to incorporate technology into the existing business process (Johnson et al, 2022). However, a number of studies reflect significant obstacles and issues, such as inadequate training of faculty members (Aldossary et al, 2020), failure to follow up and monitor challenges for adopting AI (Albasalah et al, 2021), stress and pressure among teachers due to feeling AI is challenging their position , as well as the scarcity of resources, lack of investment in AI, poor interest in college administration, lack of knowledge, and a limited number of studies that are associated with the AI applications (Mohammad et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The Future of Education with Artificial Intelligence and Machine Learning in the Arab World: A Systematic Review of Opportunities and Challenges 26 design interactive curricula, exercises, quizzes, exams and assessments (Johnson, et al (2022). AI can also contribute to the development of digital learning resources, such as adaptive textbooks, virtual labs, and multimedia materials that enhance student engagement and understanding.…”
Section: Resultsmentioning
confidence: 99%
“…Cultural barriers: The cultural context of the Arab world may pose significant challenges to the adoption of AI in education, including social norms, values, and attitudes towards technology. The wrong idea that AI will replace human beings is a milestone challenge which leads to resistance and refusal to use it (Johnson, et al 2022). 4.…”
Section: 2the Challenges Of Using Ai In Education In the Arab World (...mentioning
confidence: 99%
“…The research on the educational application of artificial intelligence started earlier and has a wider scope, mainly including theoretical research on educational artificial intelligence, research on AI teaching products, and research on AI to promote changes in classroom teaching and application in different disciplines [11]. Johnson, D. et al's research on the teaching of artificial intelligence towards the use of AI in the United Arab Emirates (UAE) found that it is mainly used for teaching through the understanding and analyzing the learning process to create conditions for student learning [12]. Liu, S. W. J. exploring the impact of AI on ice and snow talent development instruction, found that AI is putting smart teaching platforms to use to make students more active learners and emphasized that smart technologies can be integrated with the field of robotics [13].…”
Section: Introductionmentioning
confidence: 99%